Kewenangan Satuan Polisi Pamong Praja dalam Penegakan Hukum Penjualan Miras Ilegal untuk Mewujudkan Ketertiban Masyarakat - Hady Saparudin; Ismail; Hartana (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
This research is motivated by the widespread circulation of illegal and adulterated liquor (miras oplosan) that triggers public disorder, criminality and sexual violence. The primary issues lie in the limited judicial authority of the Municipal Police, the methods of illegal alcohol sales via social media and the weak interagency synergy in law enforcement. This study is analyzed using the Theory of Authority, Lawrence M. Friedman’s Legal System Theory and Soerjono Soekanto’s Legal Effectiveness Theory to examine the legitimacy of authority, the law enforcement system, as well as the inhibiting and supporting factors of legal effectiveness. The findings indicate that the Municipal Police’s authority is attributive, encompassing administrative supervision, non-judicial actions and judicial authority through Civil Servant Investigators (PPNS) in minor offense (Tipiring) hearings. However, law enforcement remains constrained by recidivism due to sanctions that fail to create a deterrent effect. Therefore, optimizing the authority of the Municipal Police requires regulatory reinforcement, human resource capacity building and cross-sectoral synergy with the National Police (Polri) through a Memorandum of Understanding (MoU).